The investigation of student approach to problem solving about some topics of Number Theory - (:unkn) unknown (ELSEVIER SCIENCE BV, 2011)
Number Theory is described as the center of mathematics. Divisibility, parity of numbers, prime and composite numbers are the main topics of Number Theory. The purpose of this study was to investigate the Turkish students' conception and difficulties of divisibility of numbers, prime numbers and odd and even numbers concept. Furthermore this study also explored the differences, if any, of problem solving approach to different problems in three topics. The case study was used in this study. This study showed that each student's conception of same topic is different. The different responses and difficulties were discussed in details. One possible suggestion is to use different representation of problems and emphasizing multiple ways of solutions during the instruction.
Keywords: Number Theory; Prime and Composite Number